Building research capacity collaboratively: can we take ownership of our future? - Munn, Pamela (British Educational Research Journal, 2008)
This presidential address argues that there is a pressing need in the UK to build educational research capacity at system level and to do so collaboratively. It advances three main arguments for doing so. These are (i) the increasing concentration of research resources; (ii) the dangers of increasing separation of research and initial teacher education; and (iii) the complexity of the links between research, policy and practice. Drawing on evidence about research quality and on demographic trends of academic staff in education departments, it illustrates one approach to collaborative capacity building in Scotland, the Applied Educational Research Scheme. It concludes by drawing attention to the nascent Strategic Forum for Research in Education as an important forum for monitoring the health of educational research.
Keywords: bonnes pratiques; formation des enseignants; utilisation des recherches